Nilai Patriotisme dan Non Patriotisme pada Cerita Rakyat Si Pitung dalam Implementasi Pembelajaran Sastra - Rania Silva Ardellia; Wika Soviana Devi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The values contained in folklore such as patriotism and non-patriotism values of Si Pitung story have an important role in character education and literature learning. This research aims to analyze the values of patriotism and non-patriotism in the folklore of Si Pitung, as well as its implementation in literary education. The location of this research is Tanjung Priok, North Jakarta. The subjects of this research are Si Pitung as the main character and Mr. Salasa Dharma Utama as a historical figure. The research method used is descriptive qualitative research method. The results of this research are patriotism values contained in the folklore of Si Pitung are love for the country, self-sacrifice, courage, never give up, volunteerism, and justice and equality. While the non-patriotism values contained in the folklore of Si Pitung are violence, criminal, and betrayal. The patriotism and non- patriotism values of Si Pitung folklore can be implemented in literature learning through several learning methods, namely analysis model, inductive model through class discussion, strata mode, synectic model, sociodrama model, and presentation.